2015
DOI: 10.1142/s0218194015400367
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Causes of Architecture Changes Using OSS Mailing Lists

Abstract: The causes of architecture changes can tell about why architecture changes, and this knowledge can be captured to prevent architecture knowledge vaporization and architecture degeneration. But the causes are not always known, especially in open source software (OSS) development. This makes it very hard to understand the underlying reasons for the architecture changes and design appropriate modifications. Architecture information is communicated in development mailing lists of OSS projects. To explore the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, the amount of architectural threads communicated before the first stable release in ArgoUML is 65.2% and after the first stable release in Hibernate is 88.4%. In our previous work [15], we found that 89.1% architecture changes happened before the first stable release in ArgoUML and 54.3% architecture changes happened after the first stable release in Hibernate, which is positively related to the results of RQ3. Architecture information communication precedes architecture changes, and consequently the amount of architecture information communication indicates the frequency of architecture changes.…”
Section: Implications For Oss Architectingmentioning
confidence: 68%
See 2 more Smart Citations
“…For example, the amount of architectural threads communicated before the first stable release in ArgoUML is 65.2% and after the first stable release in Hibernate is 88.4%. In our previous work [15], we found that 89.1% architecture changes happened before the first stable release in ArgoUML and 54.3% architecture changes happened after the first stable release in Hibernate, which is positively related to the results of RQ3. Architecture information communication precedes architecture changes, and consequently the amount of architecture information communication indicates the frequency of architecture changes.…”
Section: Implications For Oss Architectingmentioning
confidence: 68%
“…Requirements and architecture were discussed at different abstraction levels, and consequently we classified the 23 discussion subtopics into four categories: architecture topic (i.e., specific design topics about the architecture), abstraction level (i.e., the level of the architecture artifacts discussed in architecture information communication), external quality requirement (i.e., the quality characteristics of a system from the perspective of its users satisfied by architecture changes), and internal quality requirement (i.e., the quality characteristics of a system from the perspective of its developers satisfied by architecture changes). Table 5 provides the detailed descriptions and examples of the 4 categories and 23 subtopics, which are an extension of the codes identified in our previous work that specifically focuses on the causes of architecture changes communicated in mailing lists [15]. The percentages of each subtopic (i.e., content of architecture information communication) communicated in architectural threads before and after the first stable release (BFR and AFR) in ArgoUML and Hibernate are shown in Fig.…”
Section: Architecture Information Communicated During Development (What)mentioning
confidence: 99%
See 1 more Smart Citation